KANDUNGAN SERAT KASAR HIJAUAN RAMI (Boehmeria nivea L. Gaud) PADA BERBAGAI UMUR PEMOTONGAN - Iin Susilawati; Sari Suryanah; Budi Ayuningsih; Lizah Khairani; Ana Rochana Tarmidi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
This study was aimed to determine the effect of different cutting age on the crude fiber content of ramie (Boehmeria nivea L. Gaud) as forage, and to know the optimum cutting age of ramie for ruminant feed. The research was carried out in Margamulya Village, Cikandang District, Garut Regency, from August to October 2018. Crude fiber analysis was carried out at the Ruminant Animal Nutrition Laboratory and Animal Food Chemistry, Faculty of Animal Husbandry, Padjadjaran University. The study used a completely randomized design with four (4) treatments and five (5) replications, i.e. P1 = 15 days of cutting age, P2 = 30 days of cutting age, P3 = 45 days of cutting age, P4 = 60 days of cutting age. To find out the differences in effects between treatments, Duncan's multiple range test was carried out. The results showed that the cutting age affected the crude fiber content of ramie. The older cutting age had the increased crude fiber content. The optimum cutting frequency of ramie for forage was 30 days with ADF content 38%, NDF 53.2%, hemicellulose 34.1%, cellulose 14.8% and lignin 4.0%.